Pengembangan Instrumen Penilaian Berbasis Higher Order Thinking Skills (HOTS) Pada Mata Pelajaran Kearsipan Jurusan OTKP Di SMKN 1 Sooko Mojokerto - Sella Rodiana; Triesninda Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
AbstractThis study to purpose (1) the process of developing assessment instruments based on higher order thinking skills (HOTS) in the archive material of the OTKP major at SMKN 1 Sooko Mojokerto, (2) the feasibilty of assessment instrument based on higher order thinking skills (HOTS) on the archive material OTKP major at SMKN 1 Sooko Mojokerto (3) high level thinking skills of students in the Archive material OTKP major at SMKN 1 Sooko Mojokerto. The method used in this study is Research and Development (R&D). The development model used is the Sugiyono development model which consists of seven stages, namely the potential and problem stage, the data collection stage, the product design stage, the design validation stage, the design revision stage, the product trial stage, and the product revision stage. This product was tested on class X OTKP 1, 2, and 3 at SMKN 1 Sooko Mojokerto. The results showed that the feasibility of an instrument of assessment based on higher order thinking skills based on the results of validation by material experts, evaluators, and linguists obtained an average percentage of 90% with a very strong category. Feasibility quantitatively trials that include validity, reliability, level of difficulty, different power, and the deception of the questions to produce 25 multiple choice questions with the best criteria. Based on trial it can be seen that 61,7% of class X OTKP students have the ability to think at a high level in the medium category.